2017
DOI: 10.1007/s10278-017-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural Language Processing of Free-Text Radiology Reports to Identify Type 1 Modic Endplate Changes

Abstract: Electronic medical record (EMR) systems provide easy access to radiology reports and offer great potential to support quality improvement efforts and clinical research. Harnessing the full potential of the EMR requires scalable approaches such as natural language processing (NLP) to convert text into variables used for evaluation or analysis. Our goal was to determine the feasibility of using NLP to identify patients with Type 1 Modic endplate changes using clinical reports of magnetic resonance (MR) imaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Prior work for finding medication mentions has focused on written clinical reports. [47][48][49][50][51] Our error analysis suggests that baseline approaches, which rely on dictionaries, struggle with patient-clinician conversational text because of language like filler words (for example, "aha" and "hmm") matching with abbreviations for medications, and the fact that common conversational words are often used as medication names.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work for finding medication mentions has focused on written clinical reports. [47][48][49][50][51] Our error analysis suggests that baseline approaches, which rely on dictionaries, struggle with patient-clinician conversational text because of language like filler words (for example, "aha" and "hmm") matching with abbreviations for medications, and the fact that common conversational words are often used as medication names.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been used to predict hospital readmissions, [43] future radiology utilizations, [44] and characterization of significance, change, and urgency of clinical findings in medical records. [45][46][47][48][49] As such, we plan to develop a recording system for patients that applies NLP methods to unstructured clinic visit recordings. [50] In this paper, we describe an approach to extract mentions of medication names in transcripts of clinic visit audio recordings.…”
Section: Background and Significancementioning
confidence: 99%
“…We found that DL using a document-level approach was a better method for predicting the prognosis of AIS patients using brain MRI free text reports than using word- or sentence-level approaches. Several NLP-based ML studies have shown good classification performance in differentiating certain disease phenotypes from the corresponding free text MRI reports with a word-level approach alone [ 22 , 23 , 24 , 25 ]. However, the studies did not implement DL algorithms to predict their own targets.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Such structured reports maximize objectivity and reduce variability of prose text most often used in reports and enhancing the link between radiology findings and treatment suggestions. 72 Structured radiology reports may either be automatically generated from unstructured human radiology reports using advanced language processing, 73,74 which does not require any cultural changes in clinical radiologic practice at the institutions, or they could be achieved by the more difficult cultural transition to structured reporting by radiologists. Structured reports generated by the Bionic Radiologist described above would also facilitate the linkage of the results to the wording of evidence-based and personalized treatment recommendations.…”
Section: Impact Of the Bionic Radiologistmentioning
confidence: 99%